COMPARITIVE STUDY OF HEPATOPROTECTIVE ACTIVITY OF ACANTHOSPERMUM HISPIDUM PLANT EXTRACT AND HERBAL NIOSOMAL SUSPENSION AGAINST ANTI-TUBERCULAR DRUG INDUCED HEPATOTOXICITY IN RATS - N, Himaja (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Compare the hepatoprotective activity of Acanthospermum hispidum ethanolic extract (AHEE) and herbal niosomal suspension (HNS) against hepatotoxicity. Methods: AHEE and HNS were investigated against hepatotoxicity produced by administering a combination of four anti-tubercular drugs (ATDs) isoniazid (27 mg/kg), rifampin (40 mg/kg), pyrazinamide (66 mg/kg), and ethambutol (53 mg/kg) for the period of 28 days by oral route in rats. AHEE (400 mg/kg) and HNS (400 mg/kg) were administered along with 1 hr prior administration of ATDs once daily to five groups (six animals per group) of Albino Wistar rats weighing about 150-200 g. Silymarin was used as a standard drug (100 mg/kg p.o.). Liver biomarkers such as serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, alkaline phosphatase, total bilirubin, and total protein were elevated indicating the induction of hepatotoxicity in experimental animals. Results: The AHEE and HNS prevented the hepatotoxic effects of the combination of isoniazid, rifampin, pyrazinamide, and ethambutol on the above serum parameters. Histopathological studies of liver and liver biomarker estimations also supported the hepatoprotective effect of AHEE and HNS. Conclusion: The protective effect of HNS was found to be significant when compared to standard and AHEE. Keywords: Hepatoprotective, Acanthospermum hispidum, Isoniazid, Silymarin, Herbal niosomal suspension.